2000
DOI: 10.1063/1.1316036
|View full text |Cite
|
Sign up to set email alerts
|

Momentum space densities for the beryllium isoelectronic series

Abstract: Articles you may be interested inOne-and two-body densities of carbon isoelectronic series in their low-lying multiplet states from explicitly correlated wave functions Electron correlation and noninteracting v -representability in density functional theory: The Be isoelectronic series One-and two-body densities in momentum space have been calculated for the atomic beryllium isoelectronic series starting from explicitly correlated multideterminant wave functions. The effects of electronic correlations have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
(10 reference statements)
2
8
0
Order By: Relevance
“…The difference ⌬H ( ) is positive at 0Ͻ Ͻ0.80 and 1.79Ͻ Ͻ7.37, whereas it is negative at 0.80Ͻ Ͻ1.79 and Ͼ7.37. An analogous correlation effect was previously observed by Gálvez et al 25 The predominant contribution of the electron correlation is the density shift from a large-to a small-region, in accord with the change in the intracule moments ͗ n ͘ discussed previously. The electron correlation effect works to reduce the average distance ͗ ͘ of two electrons in momentum space; an opposite result observed for ͗u͘ in position space.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…The difference ⌬H ( ) is positive at 0Ͻ Ͻ0.80 and 1.79Ͻ Ͻ7.37, whereas it is negative at 0.80Ͻ Ͻ1.79 and Ͼ7.37. An analogous correlation effect was previously observed by Gálvez et al 25 The predominant contribution of the electron correlation is the density shift from a large-to a small-region, in accord with the change in the intracule moments ͗ n ͘ discussed previously. The electron correlation effect works to reduce the average distance ͗ ͘ of two electrons in momentum space; an opposite result observed for ͗u͘ in position space.…”
Section: Resultssupporting
confidence: 72%
“…When the consistency of the momentum-space intracule and extracule properties is checked by means of ␦ mom ͓Eq. ͑5b͔͒, we find that ␦ mom is zero for the present and Hartree-Fock results, whereas it is nonzero for the results of Sarsa et al 23,24 and of Gálvez et al 25 The statistical uncertainty was not reported for the electron-pair moments in momentum space. Judging from the total energies, virial errors, and ␦ mom values, we consider that the present MCHF results are most accurate among the three sets of available data summarized in Table II.…”
Section: Resultsmentioning
confidence: 44%
See 2 more Smart Citations
“…The variational Monte Carlo (VMC) method constitutes an efficient alternative to obtain both accurate trial wave functions and atomic properties 24. In general, the calculation is carried out in position space but the Monte Carlo can be extended to calculate local and global momentum space properties 25–28. For most of the VMC applications to quantum chemistry the trial wave functions are obtained by minimizing the variance of the local energy instead of the energy itself.…”
Section: Introductionmentioning
confidence: 99%